2005
DOI: 10.1148/radiol.2361040158
|View full text |Cite
|
Sign up to set email alerts
|

Hydronephrotic Kidney: Pediatric Three-dimensional US for Relative Renal Size Assessment—Initial Experience

Abstract: Initial experience with renal 3D US indicates that it is an accurate method for assessment of renal parenchymal volume and relative renal size, provided there is no acute renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…7). When performed in both kidneys, split renal parenchymal volume can be calculated, which has been found comparable to results from DMSA scintigraphy and MR urography [22]. As renal parenchymal Fig.…”
Section: D Urogenital Sonographysupporting
confidence: 69%
“…7). When performed in both kidneys, split renal parenchymal volume can be calculated, which has been found comparable to results from DMSA scintigraphy and MR urography [22]. As renal parenchymal Fig.…”
Section: D Urogenital Sonographysupporting
confidence: 69%
“…Since serum Cys-C levels are frequently superior to serum creatinine levels as an index of renal function [95] with some limitations, it might be introduced as a marker of renal function and follow-up in these patients. Moreover, low renal volume detected by ultrasound measurement of renal length [96, 97] and 3-dimensional ultrasound volume [98, 99] might represent suitable parameters of reduced renal reserve in newborns and children. Scintigraphic measurement may provide a comparison of the renal reserve between kidneys and their relative variation by age in congenital unilateral reduced renal reserve [63].…”
Section: Detection Of Reduced Nephron Reservementioning
confidence: 99%
“…It has been shown to provide greater anatomical detail and comparable functional studies than ultrasound, scintigraphy and cystourography [14][15][16]. The assessment of renal volume by MRI has been reported in a number of studies [17][18][19][20][21][22][23]. Animal studies have shown that MRI is accurate to within 5% of the renal volume [18,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of renal volume by MRI has been reported in a number of studies [17][18][19][20][21][22][23]. Animal studies have shown that MRI is accurate to within 5% of the renal volume [18,19,23]. In adult human studies, 2D ultrasound using an ellipsoid formula to determine volume was not as accurate as MRI [21], whereas 3D ultrasound was comparable [22].…”
Section: Introductionmentioning
confidence: 99%